Effects of wire feed conditions on in situ alloying and additive layer manufacturing of titanium aluminides using gas tungsten arc welding. Issue 17 (12th August 2014) - Ma, Yan; Cuiuri, Dominic; Hoye, Nicholas; Li, Huijun; Pan, Zengxi
Abstract